Joint customer data acquisition and sharing among rivals - Nicola Jentzsch; Geza Sapi; Irina Suleymanova (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
It is increasingly observable that in different industries competitors jointly acquire and share customer data. We propose a modified Hotelling model with two-dimensional consumer heterogeneity to analyze the incentives for such agreements and their welfare implications. In our model the incentives of firms for data acquisition and sharing depend on the willingness of consumers to switch brands. Firms jointly collect data on transportation cost parameters when consumers are relatively immobile between brands. However, the firms are unlikely to cooperatively acquire such data, when consumers are relatively mobile. Incentives to share information depend on the portfolio of data firms hold and consumer mobility. Data sharing arises with relatively mobile and immobile consumers - it is neutral for consumers in the former case, but reduces consumer surplus in the latter. Competition authorities ought to scrutinize such cooperation agreements on a case-by-case basis and devote special attention to consumer switching behavior.
Keywords: D43; L13; L15; O30; 330; Information Sharing; Data Acquisition; Price Discrimination; Wissenstransfer; Marktforschung; Unternehmenskooperation; Preisdifferenzierung; Wechselkosten; Wohlfahrtseffekt; Theorie